2017
DOI: 10.3340/jkns.2015.0506.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between Total Disc Replacement and Posterior Foraminotomy for Posterolateral Soft Disc Herniation with Unilateral Radiculopathy : Clinical and Biomechanical Results of a Minimum 5 Years Follow-up

Abstract: ObjectiveTo compare the clinical outcomes and biomechanical effects of total disc replacement (TDR) and posterior cervical foraminotomy (PCF) and to propose relative inclusion criteria.MethodsThirty-five patients who underwent surgery between 2006 and 2008 were included. All patients had single-level disease and only radiculopathy. The overall sagittal balance and angle and height of a functional segmental unit (FSU; upper and lower vertebral body of the operative lesion) were assessed by preoperative and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Two studies were included that met inclusion criteria and directly compared outcomes between patients undergoing MIS-PCF and TDA ( Table 3 ). 57 , 58 Both studies were retrospective cohort series. Kim et al 58 2017 included 17 patients who underwent TDA with a Prestige LP cervical disc (Medtronic Sofamor Danek, Memphis, TN) and compared outcomes to 18 patients who underwent microscopic MIS-PCF with a tubular retractor system approach.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies were included that met inclusion criteria and directly compared outcomes between patients undergoing MIS-PCF and TDA ( Table 3 ). 57 , 58 Both studies were retrospective cohort series. Kim et al 58 2017 included 17 patients who underwent TDA with a Prestige LP cervical disc (Medtronic Sofamor Danek, Memphis, TN) and compared outcomes to 18 patients who underwent microscopic MIS-PCF with a tubular retractor system approach.…”
Section: Resultsmentioning
confidence: 99%
“…Operative time ranged from 90.3 to 106.7 minutes in the TDA group compared to 77.4 to 93.9 minutes in the MIS-PCF group. 57,58 The relationship was statistically significant with a shorter mean operative time in the MIS-PCF group in Kim et al 2017. 58 Mean postoperative length of stay ranged from 103.2 to 165.6 hours in the TDA group and 93.6 to 98.4 hours in the MIS-PCF group.…”
Section: Mis-pcf Compared To Tdamentioning
confidence: 89%
See 2 more Smart Citations
“…Secondly, the previous surgery in 32 cases (86.4%) was ACDF and 12 (37.5%) of these were performed using a standalone technique. ACDF is a widely accepted standard surgery for cervical spondylosis; however, recent studies suggest that the ROM at adjacent levels is significantly higher than that obtained with CDR or PCF by fixing the ROM for the index level 11,17) . Han et al 8) reported that the stand-alone ACDF group showed more frequent segmental subsidence and cervical kyphosis than the conventional ACDF group.…”
Section: Discussionmentioning
confidence: 99%